2011
DOI: 10.1111/j.1475-1313.2011.00834.x
|View full text |Cite
|
Sign up to set email alerts
|

Computer vision syndrome: a review of ocular causes and potential treatments

Abstract: Computer vision syndrome (CVS) is the combination of eye and vision problems associated with the use of computers. In modern western society the use of computers for both vocational and avocational activities is almost universal. However, CVS may have a significant impact not only on visual comfort but also occupational productivity since between 64% and 90% of computer users experience visual symptoms which may include eyestrain, headaches, ocular discomfort, dry eye, diplopia and blurred vision either at nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
450
4
33

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 527 publications
(500 citation statements)
references
References 79 publications
13
450
4
33
Order By: Relevance
“…The correlation between asthenopia and digital devices abuse has been widely reported and classified in heterogeneous population into internal ocular symptoms (strain and ache), external ocular symptoms (dryness, irritation, burning), visual symptoms (blur, double vision) and musculoskeletal symptoms (neck and shoulder pain) [1][2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation between asthenopia and digital devices abuse has been widely reported and classified in heterogeneous population into internal ocular symptoms (strain and ache), external ocular symptoms (dryness, irritation, burning), visual symptoms (blur, double vision) and musculoskeletal symptoms (neck and shoulder pain) [1][2].…”
Section: Discussionmentioning
confidence: 99%
“…Smartphone, in particular, has become the most used device that involving everyone attention during travelling, work or school activities, at home, to dinner table, restroom and even to bed before sleeping [1][2].…”
Section: Introductionmentioning
confidence: 99%
“…Some subjective measuring methods of simulator sickness (e.g., SSQ) include eye fatigue and discomfort as part of the scales. The effects of using standard non-wearable displays have been relatively well-established as the computer vision syndrome [20]. Regarding HMD, previous studies have examined its effects on visual perception (e.g., flicker fusion frequency, distance estimation), subjective comfort (e.g., fatigue, comfort), and visual acuity [21].…”
Section: Increase the Degrees Of Immersion And Interaction (Especiallmentioning
confidence: 99%
“…In both years, it was reported that the percentage of workers who feel stressed increased as their daily or consecutive work hours became longer. The increasing use of computers is believed to have caused computer-related disorders (CRDs), such as eye fatigue, stiff shoulders, upper extremity pain, lower back pain, and mental stress [3,4]. Factors that can contribute to these conditions include the setting of the computer screen, which affects working posture [5], operating the computer for extended periods [6][7][8], and tasks that require repetitive and monotonous motions [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%